PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MAHASISWA PGSD UNIVERSITAS RIAU PADA MATERI PECAHAN DENGAN PENDEKATAN MODEL METHOD - Fendrik, Muhammad (Jurnal Pendidikan Guru, 2018)
This research is motivated by the number of students who have difficulty in performing arithmetic operations on the fractional material in the context of the story of a story that strengthens the students to be able to solve these problems. This can be implemented in many ways that provide only limited explanations. This study was conducted on PGSD students who are prospective elementary school teachers who will teach elementary school students, so it can be used as a benchmark to determine the success and weakness of students in completing the subjects of elementary school mathematics. Method of modeling the use of ways to overcome problems that exist in everyday life. This study was conducted in the odd semester of 2016/2017. The subject of this research is PGSD student of FKIP Universitas Riau in third semester (student of class of 2015). The design of this study was quasi experimental nonequivalent control group, because the respondents in this study were not randomly selected, the researchers used the existing classes. The active ability of students of PGSD FKIP University of Riau on fractions through model approach of improvement method can be proved by the improvement of students ability of PGSD FKIP Universitas Riau from average pretest score 53,30 to 70,69 on average of posttest score, with an average score increase of 0.37 in the medium category.